Saksenaea erythrospora, an emerging mucoralean fungus causing severe necrotizing skin and soft tissue infections – a study from a tertiary care hospital in north India*. Issue 3 (4th March 2017) - Chander, Jagdish; Singla, Nidhi; Kaur, Mandeep; Punia, Rajpal Singh; Attri, Ashok; Alastruey-Izquierdo, Ana; Cano-Lira, José F.; Stchigel, Alberto Miguel; Guarro, Josep
Abstract: Background: Saksenaea erythrospora is an emerging and recently described pathogenic fungus mainly causing invasive cutaneous infections. Globally, very few human cases, caused by S. erythrospora, have been reported. In India, among the genus Saksenaea, S. vasiformis was the only reported pathogenic species, until recently when a case of fungal rhinosinusitis was reported to be caused by S. erythrospora . We observed five human cases of necrotizing skin and soft tissue infections caused by S. erythrospora following traumatic implantation over 1-year study period. Methods: The study was conducted for a year observing the causative role of Saksenaea species in primary cutaneous necrotizing infections. The clinical entities were diagnosed by both microbiological and histopathological examination of the skin biopsies. The final identification of fungal strains was done by comparing internal transcribed spacer (ITS) and D1–D2 domains of the LSU (larger subunit) of the nuclear ribosomal RNA (rRNA) sequences with those of type strains of the different species of Saksenaea . Results: Out of total 23 cases of necrotizing skin and soft tissue infections, 5 were caused by S. erythrospora . Intramuscular injection into the gluteal region was the predisposing factor in four patients, while upper limb involvement, following medicated adhesive tape application, was seen in one patient. All patients were treated with liposomal amphotericin B (LAMB) along with extensive debridement of necrotic tissues. Four patients responded well however one died. Conclusion: Saksenaea erythrospora is an emerging mucoralean fungus isolated in India among patients undergoing inadvertent I/M injections entailing necrotizing fasciitis at the local site.